2013
DOI: 10.15580/gjss.2013.3.122112339
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility to Domestic Energy among Rural Households: Case Study of Damboa Wagaram Ward of Damboa Local Government Area of Borno State, Nigeria

Abstract: The objective of this study was to analyze the accessibility of rural household to fuelwood in Dambao Wagaram Ward of Borno State, Nigeria. Forty households were randomly selected from where respondents for the study were obtained. Data obtained from the study were analyzed by the use of descriptive statistics. The result showed that 97.5% of respondents used fuelwood solely or complimented with other sources of domestic energy like cow dung or corn stalk. The quantity of fuelwood consumed by respondent househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Most respondents preferred charcoal (61%) for their fish roasting business against other energy sources such as firewood (27%), gas (4%) and others (8%) as shown in figure 4 below. The findings agreed with Maina et al (2017) and Ojo and Chuffor (2013) whose studies observed that basic energy sources like fuel wood/charcoal were the most common sources of domestic energy, thus this preferred energy sources as no standard price. When asked the reason for their energy preferences, most respondents mentioned readily available (36%), convenience for their business (33%), efficiency (18%), affordability (10%) compare to other energy sources while 3% of the respondents mentioned others as seen in figure 5 below.…”
Section: Respondents Energy Preferencessupporting
confidence: 90%
“…Most respondents preferred charcoal (61%) for their fish roasting business against other energy sources such as firewood (27%), gas (4%) and others (8%) as shown in figure 4 below. The findings agreed with Maina et al (2017) and Ojo and Chuffor (2013) whose studies observed that basic energy sources like fuel wood/charcoal were the most common sources of domestic energy, thus this preferred energy sources as no standard price. When asked the reason for their energy preferences, most respondents mentioned readily available (36%), convenience for their business (33%), efficiency (18%), affordability (10%) compare to other energy sources while 3% of the respondents mentioned others as seen in figure 5 below.…”
Section: Respondents Energy Preferencessupporting
confidence: 90%
“…The cost of electricity indicates that there was an increase from ₦2.30/KWH to ₦11.75/KWH between 2000 to 2012 in Nigeria with only a very small percentage connected to the national grid (Shittu et al, 2004;Babanyara and Saleh, 2010;Sambo, 2010;Abdrazack et al, 2012;Oyekale et al, 2012;Audu, 2013). This has pushed up the percentage of households that use other sources of fuels for cooking (Taru et al, 2011;Ojo and Chuffor, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ojo et al [13] examined the effects of women's socio-economic characteristics on household fuel consumption in Damboa local government area of Borno State, North-east Nigeria using multiple regression analysis on a sample of 40 households. The results showed that the quantity of fuelwood consumed by households was determined by income, age, family size and marital status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most existing studies in relation to fuelwood consumption in Nigeria tend to focus on rural populations [10][11][12][13]. Only a few similar studies such as Abdulhamid, Abdullahi, Safiyanu, Suleiman, Shu'aib and Dambatta [14], Ebe [15] specifically covered urban areas in the southeastern and North-central parts of the country respectively.…”
Section: Introductionmentioning
confidence: 99%